Chylothorax as a complication of congenital myotonic dystrophy: A retrospective cohort study. (July 2021) - Kambara, Masanori; Ibara, Satoshi
Abstract: Background: The association between congenital myotonic dystrophy (CMD) and chylothorax is poorly recognized. Aims: To evaluate the proportion of chylothorax in infants with CMD compared to its prevalence in infants without CMD. Study design: Single-center, retrospective, cohort study. Subjects: Infants managed at a neonatal intensive care unit from 2003 to 2019. Outcome measures: CMD was diagnosed using Southern blot for the quantification of CTG repeats in the dystrophia myotonica protein kinase (DMPK) gene. Prenatal and postnatal data of eligible infants with CMD were collected from the patients' medical records. The primary outcome was the proportion of chylothorax. Results: While the proportion of chylothorax in eligible infants without CMD was 0.25% (27/10714), that in infants with CMD was 50% (5/10; odds ratio (OR), 386.3; 95% confidence interval (CI), 84.4–1850.8; P  < 0.001). The variables that were significantly different between infants with CMD with chylothorax and those without chylothorax were as follows: maternal age (33.0 vs. 24.8; P  = 0.005), polyhydramnios (5/5 vs 1/5; P  = 0.034), number of CTG repeats (1980 vs. 1500; P  = 0.038), duration of invasive mechanical ventilation (220 vs. 2, P  = 0.009), and duration of hospitalization (217.2 vs 68.0; P  = 0.014). The mortality rate of all eligible infants with CMD was 5/10 (50%). No variables were significantly associated with mortality. Conclusions: The proportion of chylothorax in infants with CMD was significantly higher than that in infants without CMD. Furthermore, the proportion was higher than that reported in previous studies on congenital chylothorax. This suggests that chylothorax may be frequently experienced in the clinical course of CMD. Highlights: Chylothorax is a complication of CMD but the association is poorly understood. Chylothorax may lead to adverse outcomes in infants with CMD. The proportion of chylothorax in infants with CMD was significantly higher. Those with chylothorax required a longer duration of IMV and hospitalization. Findings suggest that chylothorax may be a frequent complication of CMD.